Simulacija naleta tovornega vozila ob cestno varnostno ograjo - Borovinšek, Matej (Strojniški vestnik, 2006)
Road safety can be improved by applying appropriate road-safety barriers that prevent road-traffic participants from entering dangerous areas. In terms of preventing vehicles from veering off the road, a road-safety barrier should redirect the impacting vehicle back onto the road. In the process of doing so it should absorb as much of the vehicle's kinetic energy as possible through its deformation, so reducing the deceleration of the vehiclećs occupants. This paper considers a computer simulation of a truck's impact on a steel road-safety barrier. Parametric computer simulations were used to evaluate the different additional safety elements of the road-safety barrier. The dynamic finite-element explicit code LS-DYNA was used for this purpose. The computer simulations prove that the analyzed road-safety barrier design is strong enough to retain and redirect the truck back onto the roadway. Appropriately, the high absorption of the impacting vehicle's kinetic energy through the safety-barrier deformation is observed at the same time, which indicates a reduction in a vehicle's deceleration, and with that, a higher safety level for the vehicle's occupants.
Keywords: LS-DYNA; varnost na cestah; ograje varnostne; analize trkov; simuliranje dinamično; prometna varnost; varnostne ograje; trki vozil; prometne nesreče